Nasopharyngeal mucoepidermoid carcinoma: a rare tumor in nasopharynx - Seong Kin, Foong; Jeing, Yong Doh; Mawaddah, Azman (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Mucoepidermoid carcinoma (MEC) is a malignant epithelial salivary gland neoplasm which consists of a mixture of mucin-producing columnar cells, epidermoid (squamous) cells and polygonal intermediate cells. Salivary gland-type carcinomas are extremely rare to be found in the nasopharynx. A 46-year-old lady presented with bilateral progressive nasal blockage and occasional epistaxis for 3 years. However, there was no neck swelling. Nasoendoscopy revealed a huge nasopharyngeal mass. Tissue biopsy in clinic setting reported of inverted papilloma. Computed tomography shows large irregular heterogenously enhancing mass in nasopharynx. Posterior septectomy was done for the access and endoscopic excision of nasopharyngeal tumor was performed. Histopathological examination confirmed the tumor is mucoepidermoid carcinoma. Postoperative adjuvant concurrent chemoradiotherapy with total of 66 Gy was commenced in view of concern of possible residual microscopic disease. Nasopharynx is an uncommon site for MEC. MEC patients seldom has enlarged neck node at presentation.Nasopharyngeal salivary gland-type carcinomas does not commonly cause cranial nerve palsy compared to nasopharyngeal carcinoma (NPC). In cases with huge nasopharyngeal mass without neck nodes and cranial nerves involvement, MEC can be a differential diagnosis. Surgical removal of gross disease and concurrent chemoradiotherapy as an adjuvant treatment for likely residual microscopic disease is the standard treatment for nasopharyngeal mucoepidermoid carcinoma.